Charcot‐Marie‐Tooth disease in children - Ezgi Saylam; Praveen Kumar Ramani; Ruthwik Duvuru; Brett Haley; Aravindhan Veerapandiyan (Annals of the Child Neurology Society, 2024)
Abstract Charcot‐Marie‐Tooth (CMT) disease represents a diverse group of inherited neuropathies with a broad spectrum of symptoms. It is the most prevalent inherited neuropathy, with an estimated prevalence ranging from 9.7 to 82 cases per 100,000 individuals. Despite this, CMT comprises only 118 of 853 inherited neuropathy entries in the Online Mendelian Inheritance in Man (OMIM) database. This comprehensive review offers a thorough examination of CMT's clinical features, subtypes, genetic underpinnings, and pathomechanisms in pediatric cases. CMT typically manifests as progressively worsening muscle weakness and atrophy, primarily affecting the distal extremities. Patients may also experience foot and ankle deformities, hand atrophy, and other systemic issues. To accurately diagnose CMT, a detailed family history, comprehensive clinical evaluation, nerve conduction studies, and relevant genetic testing are essential. Importantly, establishing a differential diagnosis is crucial during evaluation to rule out other conditions with similar presentations. This review aims to provide clinicians with a valuable resource for diagnosing and managing CMT, emphasizing the need for a streamlined and standardized approach considering advancements in genetic testing and the identification of various subtypes.